Overruled!: Implicit cues rather than an orthographic rule determine Dutch children's vowel spelling. (August 2018) - de Bree, Elise; Geelhoed, Jan; van den Boer, Madelon
Abstract: This study addressed the question why vowel spelling acquisition is relatively difficult for young Dutch spellers. A spelling rule guides vowel spelling, but implicit cues could also play a role. We evaluated the role of phonology, morphology, and orthography. Grade 1 ( N = 113) and 2 ( N = 59) children were presented with dictations of real and pseudowords differing in the degree of consistency and familiarity. Correct scores of consistent vowel spelling in Grade 1 and 2 students were near ceiling, whereas those for inconsistent vowels were low, even in Grade 2 children, who have had explicit instruction of the spelling rule. Correct scores were affected by phonological and morphological consistency, and orthographic familiarity. Effects of these implicit cues were even more pronounced in Grade 2. Findings indicate that vowel length spelling is difficult to acquire because the explicit spelling rule is overruled by various sources of implicit information. Highlights: Spelling of vowels is difficult, despite explicit instruction of spelling rules. Vowel spelling can depend on phonological, morphological and orthographic cues. Vowel spelling in words and pseudowords was assessed in Grades 1 and 2. Children rely on various sources of information rather than the explicitly taught rule. Grade 2 children who know the rule are even more likely to depend on implicit cues.